2016
DOI: 10.1111/1750-3841.13422
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Processed Functional Foods: Technological and Operational Pathways

Abstract: This paper offers a concise review of technical and operational concepts underpinning commercialization of minimally processed functional foods (FFs), foods with fresh-like qualities commanding premium prices. The growing number of permitted nutritional content/health claims, many of which relate to well-being, coupled with emerging extraction and food processing technologies offers new exciting opportunities for small and medium size enterprises (SMEs) specializing in fresh produce to play an active role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 54 publications
0
28
0
1
Order By: Relevance
“…It seems that the adjustment of the Cornelian cherry juice pH value to 3.5 from 2.8, which was the pH value of the freshly prepared juice, supported cell viability. This slight increase was made in order to ameliorate the survival of L. plantarum ATCC 14917 as other researchers have proposed [ 22 ] and fulfil the criteria of the food industry that requires minimal processing treatments [ 35 ]. On the other hand, there are reports claiming that the type of probiotic or inhibitory compounds can affect cell viability on fruit juices [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It seems that the adjustment of the Cornelian cherry juice pH value to 3.5 from 2.8, which was the pH value of the freshly prepared juice, supported cell viability. This slight increase was made in order to ameliorate the survival of L. plantarum ATCC 14917 as other researchers have proposed [ 22 ] and fulfil the criteria of the food industry that requires minimal processing treatments [ 35 ]. On the other hand, there are reports claiming that the type of probiotic or inhibitory compounds can affect cell viability on fruit juices [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are more than 100 kinds of materials, such as thermoplastics, metals, nylon, acrylic, gypsum, ceramics, and edible materials that could be used for 3DP [9][10][11][12][13][14][15][16][17]. Nevertheless, 3DP has been studied for approximately 30 years, and the development of the technology is not as universal as expected.…”
Section: Dp and Gpnsmentioning
confidence: 99%
“…Consumption of lycopene-rich foods (especially tomatoes) or dietary supplements containing this carotenoid has been repeatedly demonstrated to produce health-promoting and antiaging effects (Moran et al, 2013;Petyaev, 2016;Costa-Rodrigues et al, 2018). Nevertheless, no clarity exists on the comparative efficiency of natural foods versus traditional pure supplements (Burton-Freeman and Sesso, 2014), and new versions of functional foods that can be defined as conventional foods enriched with Systemic and skin-targeting beneficial effects of lycopene-enriched ice cream: A pilot study health-promoting components (Rodgers, 2016;Hunter and Hegele, 2017) are actively being developed and investigated. Our previous studies have demonstrated the antihypertensive and oxidative stress-reducing effects of both lycopene combined with whey protein (Petyaev et al, 2012) and lycopene-containing dark chocolate (Petyaev et al, 2014).…”
Section: Introductionmentioning
confidence: 99%